(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Extremely continental climatic conditions, characterized by significant daily and seasonal temperature changes, low air humidity and intense solar radiation, have a significant impact on the performance characteristics of hydraulic oils used in agricultural and reclamation equipment. Under these conditions, the processes of oxidation, thermal degradation and contamination of the oil are accelerated, which leads to a decrease in its lubricating, anti-corrosion and viscosity properties. The article examines the main factors of aging of hydraulic oils in extreme continental climatic conditions, analyzes the mechanisms of degradation, and also offers recommendations for the selection, operation and replacement of oils to increase the reliability and durability of equipment.